The East African Community Single Customs Territory (EACSCT) and the Movement of Goods: A Study from Rwandan Customs Posts - Vincent , Nkundabaramye; William, Nsabimana (Recent Trends in Arts and Social Studies Vol. 4, 2023)
This chapter aims to determine the level of the implementation of the East African Community Single Customs Territory (EACSCT) and assesses the extent to which the EACSCT affects the movement of goods along the Rwandan customs posts. Despite the variables that make cross-border product transportation uncertain and complicated, it is essential to global trade. To address the variables influencing the movement of products and improve trade within the area, the EAC has adopted a unified customs territory. The EAC is composed of seven partner states namely, Kenya; Uganda; Tanzania; Burundi; Rwanda; South Sudan; and Democratic Republic of Congo. However, the study was conducted in Rwanda. The latter shares borders with Uganda in the North, Tanzania in the East, Burundi in the South and Democratic Republic of Congo in the West. The study used primary data collected on the perceptions of various trading agents on the implementation of EACSCT, aspects of trade facilitation and movement of goods. The results show that, according to diverse groups of trading agents, the EACSCT is successfully implemented along the Rwandan customs checkpoints. The level of commercial facilitation is very high, and the Rwandan customs stations have greatly facilitated the transportation of commodities. The results also show that the EACSCT has had a considerable, advantageous impact on the flow of goods along Rwanda's customs stations. A replica study involving repeated observations over a long period of time is hence recommended. In addition, though the EACSCT is a trade facilitation initiative adopted at the level of the EAC community, the study covers only the Rwandan customs posts due to various reasons including available time. There is therefore a knowledge gap which may be filled by conducting a similar study including other partner states of the EAC.